Nursing care plans : (Mosby, 2003)
Loyola Univ., Chicago, IL. Comprehensive text includes 137 careplans and 58 additional nursing diagnosis care plans. Features online care plan constructor icons, the newest terminology, and is organized by body system. Bulleted-outline format. Softcover. DNLM: Patient Care Planning--Handbooks.